Analisis Determinasi Tingkat Penyerapan Tenaga Kerja Indonesia: Studi Kasus 11 Provinsi Tahun 2016-2020 - Ramadana, Dedi; Rusmin Nuryadin, Muhamad (PPJP ULM, 2024)
This study aims to simultaneously and partially analyze the effects of education, inflation and minimum wages on employment rates in 11 Indonesian provinces in 2016-2020. The research used is a quantitative approach and uses panel data. The data used comes from the official website of the Central Statistics Agency (BPS). The results of the research show that education, inflation and minimum wages are significant in terms of employment. Furthermore, education has a positive and significant effect, inflation and minimum wages have a negative and insignificant effect on employment in 11 provinces in Indonesia.